Penanganan rembesan dan perkuatan tanah menggunakan metode insitu test (pressure meter test) studi kasus : proyek Bendungan Margatig - Nora Anggraini; Endro Prasetyo Wahono; Dyah Indriana Kusumastuti (Jurusan Teknik Sipil Universitas Lampung, 2024)
The purpose of this writing is to determine the handling of seepage and soil reinforcement required in the case study of the Margatiga Dam Project, East Lampung. Based on the results of geological investigations, the Margatiga Dam is composed of quarter-old rock layers with a fragment composition in the form of fine sand - gravel, with a hardness level of soft - hard and the need for foundation repairs. Based on the lithological conditions of the Margatiga Dam Extraction Gate foundation and the Spillway building which are composed of relatively deep and quite porous alluvial sand deposits, this causes the curtain grouting results to be ineffective, therefore it is necessary to change the design to control seepage from the Grouting Curtain to the boundary wall. Based on the simulation checks in the Plaxis Software for Seepage and Excavation Staging, processing was carried out using Secant Pile and Soldier Pile with a depth of 30 meters with a stretch of 140 m and overlapping with the left side of the Embankment Curtain Goruting. and the right side 5 m. PMT results in the field show that the maximum stress in the rock layer under the spillway foundation is 0.016 MPa and 0.630 MPa.